Analisis Rasa Percaya Diri dan Burnout Atlet Bola Voli Bk Porda Putra Sumedang 2025 Sebelum Bertanding - Novi Noviyani; Aam Ali Rahman; Dewi Susilawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the psychological dynamics related to the level of self-confidence and burnout conditions in volleyball athletes in Sumedang Regency before competing. This study uses a qualitative design with a case study approach involving six male athletes who are part of the 2025 Regional Sports Week (Porda) team of Sumedang Regency. Data were collected through interviews, questionnaires, and observations, and then analyzed using triangulation techniques. The results of the study show that athletes' self-confidence is rooted in the synergy between technical competence, resilience, and spiritual efficacy, with a dominance of high self-confidence levels (66,66%) and low burnout levels (83.33%). The conclusion of this study is that high self-confidence serves as the main determinant in maintaining mental readiness and minimizing fatigue or burnout in volleyball athletes. Keywords: Volleyball, Burnout, Self-Confidence, Athlete Psychology